The role of urban greenery in the sustainable development of the city Bydgoszcz - Oleś, Magdalena; Harłoziński, Kazimierz (Journal of Education, Health and Sport, 2016)
The problem of the development concerns green areas of the city of Bydgoszcz. It determines the extent to which the urban greenery and its functioning in the city pursue the principles of sustainable development. The paper identifies the influence of urban green on important elements of urban life, ie on the society, microclimate and biodiversity of Bydgoszcz.